P112 Muscles in myositis with normal MRI appearance have higher quantitative T2 compared to those in healthy controls. (20th April 2020) - Farrow, Matthew; Biglands, John; Grainger, Andrew; Hensor, Elizabeth; O'Connor, Philip; Ladas, Andreas; Tanner, Steven; Aslam, Aamir; Emery, Paul; Tan, Ai Lyn
Abstract: Background: Myositis is an autoimmune disease which can cause a decrease in quality of life and increased mortality, presenting with muscle weakness, raised muscle enzymes and myalgia. Diagnosis is reliant on subjective clinical examinations, blood tests, conventional MRI and invasive muscle biopsies. Quantitative T2 MRI offers a non-invasive measurement of muscle oedema which could help improve the understanding of muscle pathology and potentially inform diagnosis. The aim of this study was to evaluate whether quantitative T2 MRI of muscles is sensitive enough to detect differences in myositis patients compared to healthy controls, and how it compares with current radiologist scoring methods. Methods: 16 myositis patients were recruited (10/16 female, 10 polymyositis, 6 dermatomyositis, mean age 50 ± 26), median CK 1000IU/L ± 3100IU/L, and 16 age and gender matched healthy controls were recruited. MRI of the dominant thigh were performed. Imaging was performed using a fat-suppressed turbo-spin echo sequence. Quantitative T2 measurements were obtained from regions of interest (ROI) drawn manually within the individual muscles that make up the quadriceps and hamstrings with no distinction made between affected and unaffected muscles. A mono-exponential fit was used to obtain an estimate of the T2 from each ROI. Two radiologists blinded to the diagnosis, semi-quantitatively scored by consensus the muscles on a 4-point visual scale as either no oedema (0), mild oedema (1), moderate oedema (2) or severe oedema (3). Muscle strength was assessed using an isokinetic dynamometer. Results: T2 values were higher in myositis patients compared to healthy controls [mean (SD) hamstring myositis 47.8ms (7.7ms), healthy 39.9ms (1.5ms), p < 0.001; quadriceps myositis 53.8ms (12.1ms), healthy 42.1ms (2.1ms), p < 0.001]. Quantitative T2 correlated with the radiologists' oedema scores with rs =0.7 in the hamstrings (p < 0.001) and rs =0.6 in the quadriceps (p < 0.001), with an upward trend in T2 as radiologist scored visible oedema increased. Patients who had been classified as normal by the radiologists were compared with matched healthy controls (n = 8), T2 values for patients with 'normal muscle' were still higher than those for healthy controls: mean T2 in the hamstrings (myositis 42.2ms, healthy controls 38.7ms, p = 0.004); mean T2 in the quadriceps (myositis 43.9ms, healthy controls 40.1ms, p = 0.001). T2 was inversely correlated with muscle strength in all participants. Conclusion: Quantitative T2 measurements can detect muscle differences between myositis patients and healthy control groups, which suggests that this measurement could be used as an objective method to monitor muscles. They are also sensitive to differences that may not be detected by radiologists. This suggests that subtle systemic changes in muscle in myositis patients, which go undetected in semi-quantitative visual scoring, can be detected using quantitative T2 measurements. This shows the potential for T2 measurements to be a diagnostic measure in the diagnosis and management of myositis. Disclosures: M. Farrow None. J. Biglands None. A. Grainger None. E. Hensor None. P. O'Connor None. A. Ladas None. S. Tanner None. A. Aslam None. P. Emery None. A. Tan None.